A Characterization of Symmetric Stable Distributions. (17th April 2016) - Ejsmont, Wiktor
Abstract : Characterization problems in probability are studied here. Using the characteristic function of an additive convolution we generalize some known characterizations of the normal distribution to stable distributions. More precisely, if a distribution of a linear form depends only on the sum of powers of the certain parameters, then we obtain symmetric stable distributions.